A microbial emulsified repair material and method for fine cracks in concrete
By using microbial emulsification repair materials and using microbial-induced calcium carbonate precipitation technology, the problem of difficult to repair fine concrete cracks in the prior art with an opening of 0.1 mm to 0.5 mm is solved, and the cracks are quickly, high-strength and permanent repair are achieved, and the material is environmentally friendly.
Patent Information
- Application Number
- CN202411479526.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The prior art is difficult to effectively repair fine cracks in concrete, especially cracks with an opening of between 0.1 mm and 0.5 mm. The slurry permeability of traditional methods is poor and may produce harmful chemicals, affecting the environment and the health of construction workers.
A microbial emulsification repair material is used, which consists of slurry A and slurry B. Slurry A includes a suspension of microorganisms and calcium carbonate solid particles, a sodium alginate-nanofiber solution and a calcium chloride solution. Slurry B contains CaCl2 and urea. By injecting slurry B into the crack first and then injecting slurry A, the crack repair is achieved using microbial-induced calcium carbonate precipitation technology.
This method can effectively solve the problems of poor permeability of slurry and chemical composition pollution in traditional crack repair methods, achieve rapid, high-strength and permanent repair of cracks, and the materials are environmentally friendly and will not cause environmental pollution.
Smart Images

Figure CN118993765B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, and in particular to a microbial emulsified repair material and method for fine cracks in concrete. Background Art
[0002] During long-term use, concrete often develops cracks due to stress concentration, environmental erosion and other reasons. The existence of cracks will affect the durability and safety of the concrete structure, so it is very necessary to repair the cracks.
[0003] For cracks with an opening less than 0.1mm, surface sealing treatment can usually meet engineering requirements. For cracks with an opening greater than 0.5mm, existing engineering repair methods such as cement grouting can effectively solve the problem. However, for cracks with an opening between 0.1mm and 0.5mm, cement slurry has poor permeability and is difficult to fully penetrate and fill the cracks. Although chemical slurry has good permeability, it may produce harmful chemicals during use, posing a certain threat to the health of construction workers and the environment. Therefore, for cracks with an opening between 0.1mm and 0.5mm, an environmentally friendly and effective technical solution is urgently needed.
[0004] In recent years, crack repair technology based on microbial induced calcium carbonate precipitation (MICP) has gradually attracted attention. The slurry has good permeability, the mineralized product is compatible with the concrete composition, and the material is green and environmentally friendly, and will not cause environmental pollution. The present invention improves the general MICP slurry and proposes a microbial emulsified repair material, which can not only effectively solve the problems of poor slurry permeability and chemical composition pollution in traditional crack repair methods, but also achieve rapid, high-strength and permanent repair of cracks. Summary of the invention
[0005] In order to solve the technical problems raised in the background technology, the present invention provides a microbial emulsified repair material and method for fine cracks in concrete.
[0006] The present invention is implemented by the following technical scheme: a microbial emulsified repair material for fine cracks in concrete, the repair material used comprises slurry A and slurry B, wherein slurry A is a microbial emulsified repair agent, and slurry B is a binder;
[0007] Slurry A is obtained by mixing and stirring a suspension containing microorganisms and calcium carbonate solid particles, a sodium alginate-nanofiber solution and a calcium chloride solution in a certain proportion, and the components of slurry B include 1-2 mol / L CaCl2 and 1-3 mol / L urea.
[0008] Preferably, the preparation method of slurry A is as follows:
[0009] Step 1, preparing a suspension containing microorganisms and calcium carbonate solid particles;
[0010] Step 2, preparing a sodium alginate-nanofiber solution;
[0011] Step 3, preparing calcium chloride solution;
[0012] Step 4: Add the suspension containing microorganisms and calcium carbonate solid particles into the sodium alginate-nanofiber solution, stir thoroughly, then add the prepared calcium chloride solution into the mixed solution of the two, continue stirring, and obtain slurry A.
[0013] Preferably, the volume ratio of the suspension containing microorganisms and calcium carbonate solid particles, the sodium alginate-nanofiber solution, and the calcium chloride solution is 1:1-4:0.2-1.
[0014] Preferably, the specific operations of step 1 are as follows:
[0015] Mix 3-5 parts of Bacillus pasteurianus liquid and 1 part of slurry B and stir for 12 hours until the added CaCl2 is completely consumed to prepare a first solution; place the first solution in a refrigerator at 4°C to precipitate for about 8 hours; calculate the theoretical amount of calcium carbonate generated, and after removing part of the upper liquid according to the required solid-liquid ratio, stir again to form a suspension, and the required solid-liquid ratio is 5g / 100ml-30g / 100ml.
[0016] Preferably, the specific operations of step 2 are as follows:
[0017] 0.1%-10% (w / v) sodium alginate is added to distilled water, heated and stirred, and a sodium alginate solution of a certain concentration is obtained after cooling; then 0.1%-5% (w / v) nanofibers are added to distilled water, and the fibers are evenly dispersed by ultrasonic treatment and magnetic stirring to obtain a nanofiber solution of a certain concentration; the obtained sodium alginate solution and the nanofiber solution are mixed and stirred at a ratio of 1:1 to obtain a sodium alginate-nanofiber solution of the desired concentration.
[0018] Preferably, the specific operations of step 3 are as follows:
[0019] Weigh CaCl2 powder, add a certain amount of distilled water to it, stir and dissolve, and then make a calcium chloride solution in a 1L volumetric flask; the concentration of the calcium chloride solution is 0.05-0.5mol / L.
[0020] Preferably, the preparation method of slurry B is as follows: weigh a certain amount of CaCl2 and urea, add a certain amount of distilled water thereto, stir and dissolve, and then adjust the volume in a volumetric flask to obtain a binder containing 1-2 mol / L CaCl2 and 1-3 mol / L urea.
[0021] The present invention proposes an application of a microbial emulsified repair material for fine cracks in concrete, specifically: applying the material to repair micro cracks in concrete / rock, and the opening of the micro cracks is 0.1mm-0.5mm.
[0022] The present invention also proposes a method for repairing fine cracks in concrete, which utilizes the above-mentioned repair material and specifically includes the following steps:
[0023] First, seal the crack with a sealing tape; the sealing tape is made of butyl rubber tape and sponge;
[0024] Then, the grouting pipe is passed through the sealing patch and slurry B is injected into the crack to fully infiltrate the inside of the crack; then slurry A is injected, and slurry A reacts with slurry B to repair the crack;
[0025] Preferably, the volume ratio of slurry A to slurry B is 1:1-3.
[0026] Since butyl rubber tape has good waterproofness and strong adhesion, it can stick well to the surface of concrete and rock. The sponge is soaked with cementing liquid and fits tightly to the crack opening. It can prevent the loss of reaction slurry while replenishing cementing liquid for the MICP reaction in the crack. This method can repair the crack after one grouting, avoiding multiple grouting treatments.
[0027] After slurry B and slurry A are injected into the cracks in sequence, sodium alginate reacts rapidly with calcium ions to generate calcium alginate gel to quickly seal the cracks. Then, urea molecules and calcium ions in slurry B can pass through the pores of calcium alginate gel and continuously react with microorganisms in slurry A to undergo MICP mineralization. The newly generated calcium carbonate solid particles and those existing in slurry A form a nested composite structure with the calcium alginate gel. In this composite structure, calcium carbonate crystals can effectively make up for the problem of insufficient strength and easy erosion of calcium alginate gel. Nanofibers doped in this composite structure can improve the tensile strength and toughness of the repair material.
[0028] Slurry A and Slurry B have good injectability for micro cracks, can be formed in one time, and have high efficiency. They can repair cracks quickly, highly and for a long time through the combination of rigid calcium carbonate-flexible calcium alginate-tough nanofibers. The repair materials have high anti-corrosion ability.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention improves the general MICP slurry and proposes a microbial emulsified repair material, which can effectively solve the problems of poor slurry permeability, slurry loss and chemical component pollution of the environment in traditional crack repair methods.
[0031] When the present invention is used to repair cracks in on-site construction, the cracks are sealed with a replenishing sealing sticker and then a grouting pipe is inserted for grouting. The sealing sticker is composed of two materials, namely, a butyl rubber tape and a sponge. The butyl rubber tape has good waterproofness and strong adhesion and can be well attached to the surface of concrete and rock. The sponge is soaked with a binder and fits tightly with the crack opening. While preventing the loss of reaction slurry, the binder can be replenished for the MICP reaction in the crack. This method allows the crack to be repaired after one grouting and avoids multiple grouting treatments.
[0032] The present invention utilizes sodium alginate gel solution generated by rapid reaction of sodium alginate and calcium ions to increase the viscosity of the liquid and the filling rate of cracks, utilizes the generated calcium carbonate solid particles to improve the strength of the repair material, and the flexible calcium alginate gel and the rigid calcium carbonate solid particles act synergistically to achieve rapid blocking and long-term repair of concrete or rock cracks, thereby improving the anti-corrosion ability of the repair material.
[0033] The addition of the nanofibers used in the present invention can improve the tensile strength and toughness of the repair material, and the combination of rigid calcium carbonate-flexible calcium alginate-tough nanofibers can repair cracks quickly, highly and for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A microstructure diagram of the repair material proposed by the present invention;
[0035] Figure 2 A schematic diagram of the repair method proposed by the present invention;
[0036] Figure 3 is the viscosity of slurry A in three embodiments of the present invention and one comparative example;
[0037] Figure 4 Relative permeability coefficients measured in concrete block repair tests provided for three embodiments of the present invention and one comparative example. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.
[0039] Example 1: This solution proposes a microbial emulsified repair material for fine cracks in concrete. The repair material used includes slurry A and slurry B, wherein slurry A is a microbial emulsified repair agent and slurry B is a binder.
[0040] The slurry A is obtained by mixing and stirring a suspension containing microorganisms and calcium carbonate solid particles, a sodium alginate-nanofiber solution and a calcium chloride solution in a certain proportion.
[0041] The composition of slurry B includes 1-2 mol / L CaCl2 and 1-3 mol / L urea.
[0042] In this embodiment, slurry B is prepared as follows: weigh 222g CaCl2 and 120g urea, add a certain amount of distilled water and stir to dissolve, then adjust the volume in a 1L volumetric flask to obtain a binder containing 2mol / L CaCl2 and 2mol / L urea.
[0043] In this embodiment, the preparation method of slurry A is as follows:
[0044] Step 1, prepare a suspension containing microorganisms and solid calcium carbonate particles; mix 300 ml of Bacillus pasteurianus bacterial solution and 100 ml of cementing liquid (i.e. slurry B) and stir for 12 hours until the added CaCl2 is completely consumed; place the suspension in a refrigerator at 4°C to precipitate for about 8 hours; the theoretical calcium carbonate production is 20 g, and part of the upper liquid is removed according to the required solid-liquid ratio of 10 g / 100 ml, leaving 200 ml of liquid, and stir again to form a suspension.
[0045] Step 2, prepare sodium alginate-nanofiber solution; place 100 ml of distilled water on a heated magnetic stirrer, add 1 g of sodium alginate solid while stirring until the sodium alginate is completely dissolved, and obtain a sodium alginate solution with a concentration of 1% (w / v) after cooling. Then add 2 g of nanofibers to 100 ml of distilled water, stir with ultrasound to evenly disperse the fibers, and obtain a nanofiber solution with a concentration of 2% (w / v). Then mix the obtained sodium alginate solution and nanofiber solution at a ratio of 1:1 to obtain a sodium alginate-nanofiber solution of the desired concentration.
[0046] Step 3, prepare calcium chloride solution; weigh 33.3g CaCl2, add a certain amount of distilled water to it and stir to dissolve, then dilute to volume in a 1L volumetric flask to obtain 0.03mol / L calcium chloride solution.
[0047] Step 4: Use a syringe to draw 50 ml of the suspension containing microorganisms and calcium carbonate solid particles that is being stirred, add it to 50 ml of the sodium alginate-nanofiber solution that is being stirred, and then add 5 ml of 0.3 mlo / L calcium chloride solution to the obtained mixed solution. All mixing processes require continuous stirring.
[0048] Example 2: Different from Example 1, in this example, the preparation method of slurry A is as follows:
[0049] Step 1, prepare a suspension containing microorganisms and solid calcium carbonate particles; mix 300 ml of Bacillus pasteurianus bacterial solution and 100 ml of binder (i.e. slurry B) and stir for 12 hours until the added CaCl2 is completely consumed; place the suspension in a refrigerator at 4°C to precipitate for about 8 hours; the theoretical calcium carbonate production is 20 g, and part of the upper liquid is removed according to the required solid-liquid ratio of 20 g / 100 ml, leaving 100 ml of liquid, and stir again to form a suspension.
[0050] Step 2: Prepare a sodium alginate-nanofiber solution; place 100 ml of distilled water on a heated magnetic stirrer, add 2 g of sodium alginate solid while stirring until the sodium alginate is completely dissolved, and obtain a sodium alginate solution with a concentration of 1% (w / v) after cooling. Then add 4 g of nanofibers to 100 ml of distilled water, stir with ultrasound to evenly disperse the fibers, and obtain a nanofiber solution with a concentration of 2% (w / v). Then mix the obtained sodium alginate solution and nanofiber solution in a ratio of 1:1 to obtain a sodium alginate-nanofiber solution of the desired concentration.
[0051] Step 3, prepare calcium chloride solution; weigh 33.3g CaCl2, add a certain amount of distilled water to it and stir to dissolve, then dilute to volume in a 1L volumetric flask to obtain 0.03mol / L calcium chloride solution.
[0052] Step 4: Use a syringe to draw 50 ml of the suspension containing microorganisms and calcium carbonate solid particles that is being stirred, add it to 50 ml of the sodium alginate-nanofiber solution that is being stirred, and then add 5 ml of 0.3 mlo / L calcium chloride solution to the obtained mixed solution. All mixing processes require continuous stirring.
[0053] Embodiment 3: Different from other embodiments, in this embodiment, the preparation method of slurry A is as follows:
[0054] Step 1, prepare a suspension containing microorganisms and solid calcium carbonate particles; mix 300 ml of Bacillus pasteurianus bacterial solution and 100 ml of binder (i.e. slurry B) and stir for 12 hours until the added CaCl2 is completely consumed; place the suspension in a refrigerator at 4°C to precipitate for about 8 hours; the theoretical calcium carbonate production is 20 g, and part of the upper liquid is removed according to the required solid-liquid ratio of 30 g / 100 ml, leaving 67 ml of liquid, and stir again to form a suspension.
[0055] Step 2, prepare sodium alginate-nanofiber solution; place 100 ml of distilled water on a heated magnetic stirrer, add 1 g of sodium alginate solid while stirring until the sodium alginate is completely dissolved, and obtain a sodium alginate solution with a concentration of 1% (w / v) after cooling. Then add 2 g of nanofibers to 100 ml of distilled water, stir with ultrasound to evenly disperse the fibers, and obtain a nanofiber solution with a concentration of 2% (w / v). Then mix the obtained sodium alginate solution and nanofiber solution at a ratio of 1:1 to obtain a sodium alginate-nanofiber solution of the desired concentration.
[0056] Step 3, prepare calcium chloride solution; weigh 33.3g CaCl2, add a certain amount of distilled water to it and stir to dissolve, then dilute to volume in a 1L volumetric flask to obtain 0.03mol / L calcium chloride solution.
[0057] Step 4: Use a syringe to draw 50 ml of the suspension containing microorganisms and calcium carbonate solid particles that is being stirred, add it to 50 ml of the sodium alginate-nanofiber solution that is being stirred, and then add 5 ml of 0.3 mlo / L calcium chloride solution to the obtained mixed solution. All mixing processes require continuous stirring.
[0058] Comparative Example 1
[0059] The difference between Comparative Example 1 and Example 1 is that the concentration of the sodium alginate solution in step 2 is 2% (w / v), and the concentration of the nanofiber solution is 4% (w / v).
[0060] The performance and repair effect of the repair material of the present invention are tested through indoor repair tests of concrete cracks.
[0061] Test method: Figure 2 In the repair method shown in the figure, slurry B and slurry A are injected into the concrete block with a crack of 0.2-0.3 mm using a 0.3 mm needle. After slurry B and slurry A react in the crack, the microstructure of the microbial emulsified material formed is as follows: Figure 1 As shown, four different slurries A were used, namely, slurries A prepared in Examples 1-3 and Comparative Example 1, respectively. Slurry B was then injected into the crack opening at a rate of 1 ml / min using a peristaltic pump, and the permeability of the concrete specimen was recorded after 48 hours.
[0062] The viscosity test results of slurry A are as follows: Figure 3 The permeability test results are shown in Figure 4As shown. The use of repair materials can reduce the permeability coefficient of cracked concrete by 3 to 4 orders of magnitude, and the relative permeability coefficient can reach below 60%. Comparing Examples 1, 2 and 3, it is found that in Examples 2 and 3 where the solid-liquid ratio of the suspension is higher, the viscosity of slurry A is lower, but the relative permeability coefficient after repair is lower, and the repair effect is better. Comparing Example 1 with Comparative Example 1, it is found that the higher the concentration of the sodium alginate-nanofiber solution, the higher the viscosity of the slurry, the lower the relative permeability coefficient after repair, and the better the repair effect.
[0063] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A microbial emulsified repair material for fine cracks in concrete, characterized in that: The repair material used includes slurry A and slurry B, wherein slurry A is a microbial emulsified repair agent and slurry B is a cementing liquid; The slurry A is obtained by mixing and stirring a suspension containing microorganisms and calcium carbonate solid particles, a sodium alginate-nanofiber solution and a calcium chloride solution in a certain proportion, and the components of the slurry B include 1-2 mol / L CaCl2 and 1-3 mol / L urea; The opening of the concrete fine cracks is 0.1mm-0.5mm; The volume ratio of the suspension containing microorganisms and calcium carbonate solid particles, the sodium alginate-nanofiber solution, and the calcium chloride solution is 1:1-4:0.2-1.
2. A microbial emulsified repair material for fine cracks in concrete as claimed in claim 1, characterized in that: The preparation method of slurry A is as follows: Step 1, preparing a suspension containing microorganisms and calcium carbonate solid particles; Step 2, preparing a sodium alginate-nanofiber solution; Step 3, preparing calcium chloride solution; Step 4: Add the suspension containing microorganisms and calcium carbonate solid particles into the sodium alginate-nanofiber solution, stir thoroughly, then add the prepared calcium chloride solution into the mixed solution of the two, continue stirring, and obtain slurry A.
3. A microbial emulsified repair material for fine cracks in concrete as claimed in claim 2, characterized in that: The specific operations of step 1 are as follows: Mix 3-5 parts of Bacillus pasteurianus liquid and 1 part of slurry B and stir for 12 hours until the added CaCl2 is completely consumed to prepare a first solution; place the first solution in a refrigerator at 4°C to precipitate for 8 hours; calculate the theoretical amount of calcium carbonate generated, and after removing part of the upper liquid according to the required solid-liquid ratio, stir again to form a suspension, and the required solid-liquid ratio is 5g / 100ml-30g / 100ml.
4. The microbial emulsified repair material for fine cracks in concrete as claimed in claim 3, characterized in that: The specific operation of step 2 is as follows: Sodium alginate is added into distilled water, heated and stirred, and cooled to obtain a sodium alginate solution with a concentration of 0.1%-10% w / v; nanofibers are then added into distilled water, and the fibers are evenly dispersed by ultrasonic treatment and magnetic stirring to obtain a nanofiber solution with a concentration of 0.1%-5% w / v; The obtained sodium alginate solution and the nanofiber solution are then mixed and stirred at a ratio of 1:1 to obtain a sodium alginate-nanofiber solution of a desired concentration.
5. The microbial emulsified repair material for fine cracks in concrete as claimed in claim 3, characterized in that: The specific operations of step 3 are as follows: Weigh CaCl2 powder, add a certain amount of distilled water to it, stir and dissolve, and then adjust the volume in a 1L volumetric flask to prepare a calcium chloride solution; the concentration of the calcium chloride solution is 0.05-0.5 mol / L.
6. The microbial emulsified repair material for fine cracks in concrete according to claim 5, characterized in that: The preparation method of the slurry B is as follows: weigh a certain amount of CaCl2 and urea, add a certain amount of distilled water thereto, stir and dissolve, and then adjust the volume in a volumetric flask to obtain a cementing liquid containing 1-2 mol / L CaCl2 and 1-3 mol / L urea.
7. A method for repairing fine cracks in concrete, characterized in that: The method utilizes the repair material according to any one of claims 1 to 6, and specifically comprises the following steps: First, the crack is sealed with a sealing tape; the sealing tape is composed of butyl rubber tape and sponge; Then, the grouting pipe is passed through the sealing patch and slurry B is injected into the crack to fully wet the inside of the crack; then slurry A is injected, and slurry A reacts with slurry B to repair the crack.
8. A method for repairing fine cracks in concrete as claimed in claim 7, characterized in that: The volume ratio of the slurry A to the slurry B is 1:1-3.
Citation Information
Patent Citations
Concrete crack repairing material with sodium alginate immobilized microorganisms and preparation method of concrete crack repairing material
CN114213153A
Biological material for rapidly repairing concrete microcracks and preparation method thereof
CN115626790A